Mitizzazione, rappresentazione e strumentalizzazione del fiume ne Il comandante del fiume di Ubah Cristina Ali Farah - Kornacka, Barbara (Studia Romanica Posnaniensia, 2022)
The aim of the article is to analyze the motif of the river in the novel Il comandante del fiume by Ubah Cristina Ali Farah, which appears on three planes: the level of the myth, of the representation and of the literary device. The use of the river motif demonstrates its literary potential. Furthermore, the river con- firms that the two cultures involved in postcolonial literature yield a new quality due to the acceptance and inclusion of diversity. It also affirms the writer’s autonomy from both her Somali and Italian roots. Finally, the river is established as an indispensable element for the exposition and understanding of the theme dealt by this Bildungsroman.